Alpha and gamma degradation behavior of tri-n-alkyl phosphates and tris(2-methylbutyl) phosphate: A comparative study. (November 2020) - Sarkar, Subramee; Suresh, A.; Sivaraman, N.
Abstract: Extensive study on a variety of symmetric trialkyl phosphates (TalP) has revealed that tris(2-methylbutyl) phosphate (T2MBP) could be considered as a promising alternate extractant to tri- n -butyl phosphate (TBP) for various solvent extraction procedures, especially in the case of fast reactor fuel reprocessing. However, the highly radioactive nature of the dissolver solution generated from spent fuel urges for understanding the radiolytic stability of T2MBP. In this context, a comparative analysis on the alpha and gamma radiation stability of TBP and T2MBP in n -dodecane ( n -DD) has been determined by exposing the solvent to different levels of absorbed dose using 239 Pu and 60 Co sources, respectively. Similar experiments were performed with tri- n -amyl phosphate (TAP) to highlight on the effects of structure of TalP on the extent of radiation induced damage. The effects of the absorbed dose and the concentration of TalP on degree of degradation were investigated by evaluating the deviation in the extraction ability of Zr(IV) and Pu(IV) with various gamma irradiated solvent systems. In addition, the stripping studies were performed for Zr(IV) and Pu(IV) loaded organic phase (1.1 M TalP/ n -DD) before and after gamma irradiation. The results have indicated that there is an increase in the metal extraction and decrease in the metal ion stripping tendency with the increment in the absorbed gamma dose. The impact of α-degradation for 1.1 M TalP/ n -DD was studied by analyzing their plutonium retention behaviour as a function of time. Overall it has been observed that the stripping behaviour of alpha and gamma irradiated TBP and T2MBP solutions are better compared to TAP system. An attempt has also been made to identify the degradation products upon irradiation for TAP and T2MBP based systems using IR and GC-MS spectroscopic techniques. Highlights: Alpha and gamma degradation behaviour of tris(2-methylbutyl) phosphate. Influence of structure of trialkyl phosphates on α and γ degradation. Effect of extractant concentration and absorbed dose level on radiolysis. Better understanding of degraded products by spectroscopic characterization.